Rental and sale prices of agricultural lands under spatial competition - Marten Graubner; Silke Hüttel (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2024)
Much of the land economics literature has largely ignored the spatial nature of competition and related differences between farmland rental and sales markets. In this note we propose a model for price formation in both markets under a spatial competition framework. We demonstrate that price formation differs, particularly under policy-induced output price shocks. We suggest that using rent-price ratio as an approximation for expectations in the net returns of farming, based on the net present value model, may produce biased results. We conclude that estimates for the capitalization of agricultural, environmental and energy policy into farmland prices can be biased.
urn:nbn:de:kobv:11-110-18452/29097-1
Keywords: L13; Q12; Q18; 330; Land Markets; Rent-price Ratio; Spatial Competition